Whole-Blood Testing for Diagnosis of Acute Zika Virus Infections in Routine Diagnostic Setting - Voermans, Jolanda J.C. (Emerg Infect Dis, 2019)
We evaluated the benefit of whole blood versus plasma to detect acute Zika virus infections. Comparison of Zika virus quantitative reverse transcription PCR results in single timepoint whole blood–plasma pairs from 227 patients with suspected Zika virus infection resulted in confirmation of 8 additional patients with Zika virus infection.